Enhanced Electrochemical Property of Li1.2−xNaxMn0.54Ni0.13Co0.13O2 Cathode Material for the New Optoelectronic Devices - Gao, Yumei; Hui, Yuchong; Yin, Hang (Frontiers in Physics, 2021)
The Li-rich Mn-based oxide Li1.2Mn0.54Ni0.13Co0.13O2 has been extensively studied as a cathode material of the battery module for new optoelectronic devices. To improve and enhance the electrochemical performance, sodium doping is one of the effective approaches. According to the density functional theory of first-principles, the band gap, partial density of states, lithiation formation energy, electron density difference, and potential energy of electrons for Li1.2−xNaxMn0.54Ni0.13Co0.13O2 were simulated with Materials Studio, Nanodcal, and Matlab. When the sodium doping amount x = 0.10 mol, simulations show that Li1.2−xNaxMn0.54Ni0.13Co0.13O2 has a better conductivity. The potential maps of Li1.2−xNaxMn0.54Ni0.13Co0.13O2 obtained in Matlab demonstrate that the potential barrier is lower and the rate capability is enhanced after sodium doping. Results of analyses and calculations agree with the experimental result of Chaofan Yang’s group. This theoretical method could be a great avenue for the investigation of the battery application of new optoelectronic devices. Also, our findings could give some theoretical guidance for the subsequent electrochemical performance study on doping in the field of lithium-ion batteries.